The democracy and substantive justice: instrumental moral justifications of democracy on the example of R.A. Dahl's views - N. A. Shaveko (Современная наука и инновации, 2024)
The article examines the most common instrumental moral justifications of democracy. Moral justifications are understood as justifications from the point of view of a certain social ideal, and the instrumental nature of the justifications means that the social ideal differs from democracy, and democracy is justified as a way to achieve it. Three arguments given by Dahl in support of democracy are considered: 1) the people are no less competent in matters of moral truth than any ruling elite; 2) no ruling elite, even knowing moral truth, will put it into practice if it is not controlled by the people; 3) no "elite" can be defined as such by anyone except by the people themselves. All these arguments are criticized by the author of the article. It is concluded that political governance requires a number of virtues and competencies, which are inevitably more developed in some people than in others, and thus the moral validity of universal suffrage is questioned.